EFIKASI CENDAWAN Aspergillus sp. TERHADAP HAMA PENGHISAP BUAH KAKAO Helopeltis sp. (HEMIPTERA : MIRIDAE) PADA TANAMAN KAKAO - Supriyadi, Danil; Pasaru, Flora; Lakani, Irwan (AGROTEKBIS, 2017)
The aims of this research is to determine the potential of the Aspergillus sp. Palolo local isolates on the insects of Helopeltis spp.. The results of laboratory tests were used for in the field experiment, in order to know the influence of the concentration and the intensity of insect Helopeltis spp. The results of this study are expected to be used as an alternative for researchers to use entomopathogenic fungi Aspergillus sp. This research was conducted in two places, namely to research conducted phase one preliminary test performed in the laboratory of pests and plant diseases and for stage two test field, which is housed in cocoa production centers in Palolo Sigi. This study commenced from the month of May 2015 to July 2015. On the stage by looking at the concentration of the fungus Aspergillus sp. Effective in the mortality pest Helopeltis spp. In stage two were done in the field (cocoa plantations) is a continuation of research on the preliminary test effective concentration that causes mortality in test insects. The results showed that the use of a preliminary test at a concentration of 10-3, 10-5, 10-7 and 10-9 were used in the efektivity Helopeltis spp pest mortality rate is 10-5 cfu. The number of pest population concentration Helopeltis spp.. after the Aspergillus sp applied from week to week was decreased.Â Key Words: Aspergillus sp., intensity ofÂ severity, pest population.